Sunscreen spherical silicon dioxide and preparation method thereof

By chemical grafting of nano-sun protection materials on spherical porous silica, the problem of insufficient firmness of nano-sun protection materials in the prior art is solved, stable sun protection effect and higher SPF value are achieved, and the safety of sun protection materials is improved. sex.

CN119257958APending Publication Date: 2025-01-07JIANGXI KINGPOWDER TECH CO LTD

Patent Information

Application Number
CN202411381342.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The firmness of nanotitanium dioxide and nanozinc oxide in existing sunscreen materials is insufficient and it is easy to redisperse, resulting in unstable sunscreen effect and the safety of nanomaterials for skin is controversial.

Method used

Using spherical porous silica as a carrier, the nanosunscreen material is dispersed through solvents and chemical grafted, and the silane coupling agent reacts with the hydroxyl group on the surface of the silica to form Si-OH bonds to ensure the firm adhesion of the nanomaterial and form a stable Sun protection spherical silica.

Benefits of technology

It improves the stability and firmness of sunscreen materials, enhances SPF value, ensures the durability of sunscreen effects, and reduces the potential risks of nanomaterials to the skin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119257958A_ABST
    Figure CN119257958A_ABST
Patent Text Reader

Abstract

The invention discloses sunscreen spherical silicon dioxide and a preparation method thereof. Spherical porous silicon dioxide serves as a carrier of the sun-resistant spherical silicon dioxide, pores of the spherical porous silicon dioxide are filled with sun-resistant materials, the surface of the spherical porous silicon dioxide is wrapped with a sun-resistant material layer, and the surface of the sun-resistant material layer is wrapped with a silane coupling agent layer. The specific preparation method comprises the following steps: by taking spherical porous silicon dioxide as a carrier, dispersing a nano sunscreen material through a solvent, adding the nano sunscreen material into the spherical porous silicon dioxide, adsorbing the nano sunscreen material inside the spherical silicon dioxide through pore diameters, and adsorbing the redundant nano sunscreen material on the surface of the spherical silicon dioxide to obtain the nano sunscreen material. According to the preparation method, spherical silicon dioxide is taken as a raw material, a coupling agent is added for chemical grafting, a nano sunscreen material is firmly attached to the interior and the surface of the spherical silicon dioxide in a drying and calcining mode, the obtained spherical silicon dioxide has a good sunscreen effect, the process is simple, controllability is achieved, and sunscreen spherical silicon dioxide with different particle sizes can be prepared according to needs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material preparation, in particular to sunscreen spherical silica and a preparation method thereof. Background Art

[0002] Sun protection refers to taking some measures to block or absorb ultraviolet rays to prevent the skin from getting tanned or sunburned. Currently, among physical sunscreen materials, nano-titanium dioxide and nano-zinc oxide can effectively reflect ultraviolet rays and resist UVA and UVB bands, thus playing a good protective role for the skin.

[0003] In recent years, there has been increasing controversy over the safety of nanomaterials. Reports indicate that nano-scale materials may be phototoxic and nanoparticles may penetrate into the skin. In addition, neurotoxin researchers at the US Environmental Protection Agency point out that nanomaterials have an impact on certain immune cells, and the continuous release of oxygen free radical particles may cause stress and damage to healthy cells. In many countries, the use of nanomaterials has become increasingly cautious, so there is still much room for improvement in sunscreen materials.

[0004] At present, there are many domestic patents on sunscreen materials. In patent CN117426993A, a reverse wrapping method is used. First, nano titanium dioxide and lauroyl lysine are reacted to obtain a layer of wrapped material, and then nano zinc oxide and a layer of wrapped material are reacted. After ultrasonic dispersion and drying, a reverse wrapped sunscreen material is obtained. In this patent, nano titanium dioxide and lauroyl lysine, as well as nano zinc oxide, are interconnected through an organic solvent. The organic solvent will volatilize at high temperatures. Finally, the wrapping material is equivalent to a simple physical mixing. There is no firmness between nano titanium dioxide and nano zinc oxide, and it may be redispersed into nano-level materials at any time. In patent CN111450815A, nano titanium dioxide, cerium salt solid, sesbania powder and polycarboxylic acid are used as raw materials, and titanium dioxide and cerium dioxide composites are prepared by mixing, drying and calcining. This patent uses nano titanium dioxide and cerium salt as raw materials, and the composites obtained are mostly nano-level. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a sunscreen spherical silica and a preparation method thereof.

[0006] The first object of the present invention is to provide a sunscreen spherical silica, which uses spherical porous silica as a carrier, the pores of the spherical porous silica are filled with sunscreen materials, and the surface is coated with a sunscreen material layer and a silane coupling agent layer. The hydroxyl groups (-OH) on the sunscreen material and the surface of the silica are chemically grafted with Si-OH bonds formed after hydrolysis of the silane coupling agent to form O-Si-O to achieve connection.

[0007] In the present invention, Si-OH bonds are formed after hydrolysis of the silane coupling agent, and the sunscreen material and the surface of silicon dioxide also contain some hydroxyl groups (-OH). The Si-OH bonds of the silane coupling agent react with the hydroxyl groups (-OH) to form O-Si-O bonds, thereby effectively preventing the sunscreen material from falling off and maintaining the stability of the sunscreen effect.

[0008] In some embodiments of the present invention, the particle size of the spherical porous silica is 1 micron to 100 microns, preferably 1 micron to 80 microns, and more preferably 1 micron to 30 microns. The larger the particle size of the spherical porous silica, the greater its oil absorption will be, the more nanomaterials that can be adsorbed will be, and the SPF value will be relatively larger, but the larger the particle size, the worse the sphericity and hardness of the spherical silica will be. Therefore, it is not the case that the larger the particle size of the spherical porous silica, the better, so it is also necessary to reasonably regulate the size of the particle size.

[0009] In some embodiments of the present invention, the porosity of the spherical porous silica is 1% to 50%, preferably 5% to 30%.

[0010] In some embodiments of the present invention, the sunscreen material is one or more of nano titanium dioxide, nano zinc oxide, and nano cerium oxide, preferably nano titanium dioxide and nano zinc oxide.

[0011] In some embodiments of the present invention, the content of the sunscreen material accounts for 0.1-30 wt% of the mass of the spherical porous silica, preferably 1-30 wt%, and more preferably 1-20 wt%. When the amount of nanomaterials is too much, the SPF value will be higher, but it is limited by the oil absorption of spherical silica. When the solvent reaches a certain amount, it will be a peak point. If it is excessive, it will affect the adsorption rate of the nanomaterials.

[0012] The second object of the present invention is to provide a method for preparing the sunscreen spherical silica, comprising the following steps:

[0013] A spherical porous silica powder is provided, which is referred to as powder A.

[0014] The sunscreen material is mixed with a solvent and ultrasonically dispersed to obtain a suspension B;

[0015] The suspension B is sprayed into the powder A, and the powder C is obtained by complete adsorption. Then, the silane coupling agent is sprayed into the powder C, and the powder D is obtained by stirring and dispersing. The powder D is obtained by heating and drying, and the powder E is obtained.

[0016] The powder E is calcined at high temperature to obtain the sunscreen spherical silica.

[0017] In some embodiments of the present invention, the solvent includes water and an organic solvent, and the organic solvent is selected from one or more of ethyl acetate, ethanol, isopropanol, cyclohexane, silicone oil, and mineral oil; the volume ratio of water to organic solvent is 1:1 to 1:20, preferably 1:5 to 1:10, and more preferably 1:10. The amount of water needs to be moderate. If there is too little water, the coupling agent cannot be completely hydrolyzed. If there is too much water, the powder will be relatively wet, which is not conducive to the adsorption of nanomaterials.

[0018] In some embodiments of the present invention, the mass ratio of the sunscreen material to the solvent is 1:1 to 1:20; preferably 1:1 to 1:10, and more preferably 1:1 to 1:5. The amount of solvent used needs to be moderate. The more solvent, the more evenly the sunscreen material nano titanium dioxide or zinc oxide can be dispersed, which can increase the effective adsorption rate. However, the solvent content cannot be too high. Too much will cause the silicon dioxide to be too wet and agglomerated, which is not conducive to the adsorption of the nanomaterial.

[0019] The heating and drying is carried out at a temperature of 80° C. to 110° C. and for a time of 3 to 8 hours.

[0020] In some embodiments of the present invention, the silane coupling agent is selected from one or more of methyltrimethoxysilane, methyltriethoxysilane, polymethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, octyltrimethoxysilane and octyltriethoxysilane.

[0021] The amount of the silane coupling agent is 0.1-10wt% of the spherical porous silica, preferably 1-10wt%, and more preferably 1-5wt%. The coupling agent can increase the grafting rate of chemical bonds. The higher the grafting rate, the better the adsorption effect and the higher the SPF value. However, the amount of chemical bonds in each spherical silica is limited. When the amount of the coupling agent reaches a certain level, the chemical bond grafting rate will reach a maximum. If it is increased further, it will overflow, which may affect the SPF value.

[0022] In some embodiments of the present invention, the high temperature calcination temperature is 300°C to 800°C, preferably 400°C to 700°C, more preferably 500°C to 600°C; the calcination time is 1 to 10 hours, preferably 3 to 8 hours, more preferably 3 to 6 hours.

[0023] In some embodiments of the present invention, the suspension B is sprayed into the powder A or the silane coupling agent is sprayed into the powder C by spraying. The spraying method is used here to better allow the nano sunscreen material to be adsorbed through the pores of the spherical silica.

[0024] The above technical solution of the present invention has the following beneficial effects compared with the prior art:

[0025] The present invention uses spherical porous silica as a carrier, disperses the nano sunscreen material through a solvent, and then adds it into the porous spherical silica. The nano sunscreen material is adsorbed inside the spherical silica through the pore size, and the excess nano sunscreen material is adsorbed on the surface of the spherical silica. A coupling agent is then added for chemical grafting. Finally, the nano sunscreen material is firmly attached to the inside and surface of the spherical silica through drying and calcination, thereby preparing spherical silica with a sunscreen effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein

[0027] Figure 1 This is a SEM image of the sunscreen spherical silica obtained in Example 10 of the present invention. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0029] Example 1

[0030] S1. 100 g of spherical porous silica having a particle size of 1 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0031] S2. 1 g of nano-titanium dioxide was mixed with a mixed solvent of 0.1 g of water and 1 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then uniformly dispersed by ultrasonication to obtain a suspension B;

[0032] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0033] S4. Spray 1 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0034] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0035] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0036] Example 2

[0037] S1. 100 g of spherical porous silica having a particle size of 1 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0038] S2. 1 g of nano-titanium dioxide was mixed with 0.5 g of a mixed solvent of 5 g of water and isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0039] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0040] S4. Spray 1 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0041] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0042] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0043] Example 3

[0044] S1. 100 g of spherical porous silica having a particle size of 1 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0045] S2. 10 g of nano-titanium dioxide was mixed with 5 g of a mixed solvent of water and 50 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0046] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0047] S4. Spray 1 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0048] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0049] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0050] Example 4

[0051] S1. 100 g of spherical porous silica having a particle size of 1 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0052] S2. 10 g of nano-titanium dioxide was mixed with 5 g of a mixed solvent of water and 50 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0053] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0054] S4. Spray 5 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0055] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0056] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0057] Example 5

[0058] S1. 100 g of spherical porous silica having a particle size of 1 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0059] S2. 20 g of nano-titanium dioxide was mixed with a mixed solvent of 10 g of water and 100 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0060] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0061] S4. Spray 5 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0062] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0063] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0064] Example 6

[0065] S1. 100 g of spherical porous silica having a particle size of 1 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0066] S2. 1 g of nano zinc oxide was mixed with a mixed solvent of 0.5 g of water and 5 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0067] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0068] S4. Spray 1 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0069] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0070] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0071] Example 7

[0072] S1. 100 g of spherical porous silica having a particle size of 1 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0073] S2. 10 g of nano zinc oxide was mixed with a mixed solvent of 5 g of water and 50 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0074] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0075] S4. Spray 5 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0076] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0077] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0078] Example 8

[0079] S1. 100 g of spherical porous silica having a particle size of 1 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0080] S2. 20 g of nano zinc oxide was mixed with a mixed solvent of 10 g of water and 100 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0081] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0082] S4. Spray 5 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0083] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0084] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0085] Example 9

[0086] S1. 100 g of spherical porous silica having a particle size of 30 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0087] S2. 10 g of nano-titanium dioxide was mixed with 5 g of a mixed solvent of water and 50 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0088] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0089] S4. Spray 5 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0090] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0091] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0092] Example 10

[0093] S1. 100 g of spherical porous silica having a particle size of 30 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0094] S2. 20 g of nano-titanium dioxide was mixed with a mixed solvent of 10 g of water and 100 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0095] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0096] S4. Spray 5 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0097] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0098] S6. The powder E was calcined at 600°C in a muffle furnace for 5 hours, and after cooling, a sunscreen spherical silica was obtained. The obtained product was structurally characterized, and the results are shown in Figure 1 As can be seen from the figure, the nanomaterials adsorbed on the surface of the sunscreen spherical silica obtained by the present invention are very uniform and in large quantities.

[0099] Embodiment 11

[0100] S1. 100 g of spherical porous silica having a particle size of 30 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0101] S2. 10 g of nano zinc oxide was mixed with a mixed solvent of 5 g of water and 50 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0102] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0103] S4. Spray 5 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0104] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0105] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0106] Example 12

[0107] S1. 100 g of spherical porous silica having a particle size of 30 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0108] S2. 20 g of nano zinc oxide was mixed with a mixed solvent of 10 g of water and 100 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0109] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0110] S4. Spray 5 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0111] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0112] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0113] Example 13

[0114] S1. 100 g of spherical porous silica having a particle size of 30 μm and a porosity of 5% was placed in a three-necked flask and stirred slowly at 100 rpm to obtain powder A;

[0115] S2. 20 g of nano-titanium dioxide was mixed with a mixed solvent of 10 g of water and 100 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0116] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0117] S4. Spray 5 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0118] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0119] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0120] Embodiment 14

[0121] S1. 100 g of spherical porous silica having a particle size of 30 μm and a porosity of 30% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0122] S2. 20 g of nano-titanium dioxide was mixed with a mixed solvent of 10 g of water and 100 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0123] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0124] S4. Spray 5 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0125] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0126] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0127] Comparative Example 1

[0128] This comparative example is similar to Example 10, except that no coupling agent is added, that is, step S4 is missing.

[0129] S1. 100 g of spherical porous silica having a particle size of 30 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0130] S2. 20 g of nano-titanium dioxide was mixed with a mixed solvent of 10 g of water and 100 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension solution B;

[0131] S3. Spray the suspension solution B into the powder A and stir for 3 hours to allow the adsorption to be complete to obtain powder C;

[0132] S4. The temperature was then raised to 100°C and dried for 5 hours to obtain powder E;

[0133] S5. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0134] Comparative Example 2

[0135] This comparative example is similar to Example 10, except that in this comparative example, various raw materials are only mechanically mixed without stirring.

[0136] S1. 100 g of spherical porous silica having a particle size of 30 μm and a porosity of 20% was placed in a grinder, 20 g of nano-titanium dioxide was added to the grinder, and mixed thoroughly to obtain powder A;

[0137] S2. Add 5 g of coupling agent methyltrimethoxysilane to powder A, crush and mix thoroughly to obtain powder B;

[0138] S3. The powder B was transferred to an oven and heated to 100°C for drying for 5 hours to obtain powder C;

[0139] S4. Calcine powder C at 600° C. in a muffle furnace for 5 hours, and obtain a sun-proof spherical silica after cooling.

[0140] Comparative Example 3

[0141] This comparative example is similar to Example 10, except that no calcination is performed in this comparative example, that is, step S6 is missing.

[0142] S1. 100 g of spherical porous silica having a particle size of 30 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0143] S2. 20 g of nano-titanium dioxide was mixed with a mixed solvent of 10 g of water and 100 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension solution B;

[0144] S3. Spray the suspension solution B into the powder A and stir for 3 hours to allow it to be completely adsorbed to obtain powder C;

[0145] S4. Spray 5 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0146] S5. Then the temperature is raised to 100° C. and dried for 5 hours. After cooling, a sunscreen spherical silica is obtained.

[0147] Comparative Example 4

[0148] This comparative example is similar to Example 10, except that this comparative example is subjected to a crushing treatment based on Example 10.

[0149] S1. 100 g of spherical porous silica having a particle size of 30 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0150] S2. 20 g of nano-titanium dioxide was mixed with a mixed solvent of 10 g of water and 100 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension B;

[0151] S3. The suspension B is sprayed into the powder A and stirred for 3 hours to allow the powder to be completely adsorbed to obtain powder C;

[0152] S4. Spray 5 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0153] S5. Then the temperature was raised to 100°C and dried for 5 hours to obtain powder E;

[0154] S6. The powder E is calcined at 600° C. in a muffle furnace for 5 hours, and after cooling, a sun-proof spherical silica is obtained.

[0155] S7. The powder is crushed in a high-speed crusher at 2000 rpm for 30 seconds to obtain crushed sunscreen spherical silica.

[0156] Comparative Example 5

[0157] This comparative example is similar to comparative example 3, except that this comparative example is subjected to a crushing treatment based on comparative example 3.

[0158] S1. 100 g of spherical porous silica having a particle size of 30 μm and a porosity of 20% was placed in a three-necked flask and stirred at a slow speed of 100 rpm to obtain powder A;

[0159] S2. 20 g of nano-titanium dioxide was mixed with a mixed solvent of 10 g of water and 100 g of isopropanol (the volume ratio of water to isopropanol was 1:10), and then dispersed uniformly by ultrasonication to obtain a suspension solution B;

[0160] S3. Spray the suspension solution B into the powder A and stir for 3 hours to allow it to be completely adsorbed to obtain powder C;

[0161] S4. Spray 5 g of coupling agent methyltrimethoxysilane into powder C and stir for 5 hours to obtain powder D;

[0162] S5. Then the temperature is raised to 100° C. and dried for 5 hours. After cooling, a sunscreen spherical silica is obtained.

[0163] S6. The powder is crushed in a high-speed crusher at 2000 rpm for 30 seconds to obtain crushed sunscreen spherical silica.

[0164] Performance Testing

[0165] SPF value test: SPF value is an indicator of the ability of sunscreen products to resist UVB (ultraviolet rays in the middle wave). It represents how many times the skin can be exposed to the sun after using sunscreen products compared to when not using them. The Labsphere UV-2000S SPF analyzer was used for this measurement. First, it is necessary to set specific temperature and humidity conditions, then weigh an appropriate amount of sunscreen spherical silica, evenly apply it on the test board, wait for a while, and make sure it is stable before testing. First test the blank test board without sunscreen spherical silica as a benchmark, and then test the board with sunscreen spherical silica. The test report of the SPF value can be automatically generated through the calculation of the tester. The higher the SPF value, the better the sunscreen effect.

[0166] Table 1 shows the raw material dosages used in the sunscreen spherical silica in Examples 1 to 12 of the present invention, as well as the SPF test results.

[0167] Table 1 SPF test results of sunscreen spherical silica obtained in Examples and Comparative Examples

[0168]

[0169]

[0170] From the comparison between Example 1 and Example 2, it can be seen that the amount of solvent will affect the SPF value. This is because the more solvent there is, the more evenly the sunscreen material nano titanium dioxide or zinc oxide can be dispersed, which can increase the effective adsorption rate. However, the solvent content cannot be too high. Too much solvent content will cause the silicon dioxide to be too wet and agglomerated, which is not conducive to the adsorption of nanomaterials.

[0171] From the comparison between Example 2 and Example 3, Example 4 and Example 5, Example 7 and Example 8, Example 9 and Example 10, and Example 11 and Example 12, it can be seen that the amount of nano sunscreen material will affect the SPF value. Theoretically, the more nano material, the higher the SPF value will be. However, due to the oil absorption of spherical silica, when the solvent reaches a certain amount, it will be a peak point. If it is excessive, it will affect the adsorption rate of the nano material. In the embodiment of the present invention, the SPF value with 20wt% nano sunscreen material is the best.

[0172] It can be seen from Examples 3 and 4 that the amount of coupling agent used will affect the SPF value, because the coupling agent can increase the grafting rate of chemical bonds. The higher the grafting rate, the better the adsorption effect and the higher the SPF value. However, the amount of chemical bonds in each spherical silica is limited. When the amount of coupling agent reaches a certain level, the grafting rate of chemical bonds will reach a maximum. If it is increased further, it will overflow and may affect the SPF value. In the embodiment of the present invention, the SPF value with 5wt% coupling agent added is the best.

[0173] From the comparison between Example 2 and Example 6, Example 4 and Example 7, Example 5 and Example 8, Example 9 and Example 11, and Example 10 and Example 12, it can be seen that the SPF values ​​of the sunscreen materials using nano titanium dioxide and nano zinc oxide are basically the same, indicating that both raw materials can provide good sunscreen effects.

[0174] From the comparison between Example 4 and Example 9, Example 5 and Example 10, Example 7 and Example 11, and Example 8 and Example 12, the particle size of spherical silica will affect the SPF value to a certain extent. This is because, in theory, the larger the particle size of the spherical porous silica, the greater its oil absorption will be, the more nanomaterials that can be adsorbed will be, and the SPF value will be relatively larger. However, the larger the particle size, the worse the sphericity and hardness of the spherical silica will be. Therefore, it is not the case that the larger the particle size of the spherical porous silica, the better. In the embodiment of the present invention, the SPF value of the sunscreen spherical silica prepared by using spherical porous silica with a particle size of 30 microns as a carrier is the best.

[0175] From the comparison between Example 10 and Example 13 and Example 14, the porosity of spherical porous silica will affect the SPF value to a certain extent, but when the porosity reaches a certain value, the SPF value will decrease. This is because the adsorption of nanomaterials on silica is achieved through pores. The greater the porosity, the greater the adsorption rate. However, the surface of silica is limited. The larger the pores, the smaller the surface, and the nanomaterials that can be accommodated will also decrease, which will lead to a decrease in the SPF value. In the embodiment of the present invention, the SPF value of the sunscreen spherical silica prepared with spherical porous silica with a porosity of 20% as the carrier is the best.

[0176] From the comparison between Comparative Example 1 and Example 10, it can be seen that whether or not the coupling agent is added has a considerable impact on the SPF value. This is because the coupling agent plays a bridging role here, which can chemically graft the silica and the nanopowder, thereby firmly connecting them together and increasing the SPF value.

[0177] From the comparison between Comparative Example 2 and Example 10, it can be seen that the SPF value is lower in ordinary mechanical mixing. This is because the connection between the nanomaterial and the silica is not as strong as in ordinary mechanical mixing. The mechanical mixing rate is fast, and the adsorption rate and coverage rate are both low. Slow stirring can ensure its coverage rate, thus affecting the SPF value.

[0178] From the comparison between Comparative Example 3 and Example 10, it can be seen that whether or not the calcination is performed has a certain influence on the SPF value. The SPF value of the sunscreen spherical silica prepared without calcination is lower. This is because without calcination, the adsorption firmness of the nanomaterial on the spherical silica is not high and it is more likely to fall off, thus affecting the SPF value.

[0179] Comparing Comparative Example 4 with Example 10, and Comparative Example 5 with Comparative Example 3, the SPF value of the sunscreen spherical silica prepared without calcination has undergone a significant change, indicating that the sunscreen spherical silica prepared without calcination is not very firm and falls off more severely after crushing, while the SPF value of the sunscreen spherical silica prepared after calcination has no significant change, indicating that calcination is beneficial to increasing the firmness of the nanomaterial on the spherical silica.

[0180] From the above test results (Table 1), Example 10 has the best effect, that is, when the particle size of the spherical porous silica is 30 microns, the porosity is 20%, the amount of nanomaterial is 20wt% of the spherical silica, the mass ratio of nanomaterial to solvent is 1:5, and the amount of coupling agent is 5wt% of the spherical silica, the performance is optimal.

[0181] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A sunscreen spherical silica, characterized in that: Spherical porous silica is used as a carrier, the pores of the spherical porous silica are filled with sunscreen materials, the surface is coated with a sunscreen material layer and a silane coupling agent layer, and the sunscreen material and the hydroxyl groups on the surface of the silica form O-Si-O with the silane coupling agent.

2. The sunscreen spherical silica according to claim 1, characterized in that: The particle size of the spherical porous silica is 1 micron to 100 microns.

3. The sunscreen spherical silica according to claim 1, characterized in that: The porosity of the spherical porous silica is 1% to 50%.

4. The sunscreen spherical silica according to claim 1, characterized in that: The sunscreen material is one or more of nano titanium dioxide, nano zinc oxide, and nano cerium oxide.

5. The sunscreen spherical silica according to claim 1, characterized in that: The content of the sunscreen material accounts for 0.1 to 30 wt% of the mass of the spherical porous silica.

6. The method for preparing the sunscreen spherical silica according to any one of claims 1 to 5, characterized in that: The following steps are involved: Provide a spherical porous silica powder, denoted as powder A; The sunscreen material is mixed with a solvent and ultrasonically dispersed to obtain a suspension B; The suspension B is sprayed into the powder A, and the powder C is obtained by complete adsorption. Then, the silane coupling agent is sprayed into the powder C, and the powder D is obtained by stirring and dispersing. The powder D is obtained by heating and drying, and the powder E is obtained. The powder E is calcined at high temperature to obtain the sunscreen spherical silica.

7. The preparation method according to claim 6, characterized in that: The solvent includes water and an organic solvent, wherein the organic solvent is selected from one or more of ethyl acetate, ethanol, isopropanol, cyclohexane, silicone oil, and mineral oil; and the volume ratio of the water to the organic solvent is 1:1 to 1:

20.

8. The preparation method according to claim 6, characterized in that: The mass ratio of the sunscreen material to the solvent is 1:1 to 1:20; The heating and drying is performed at a temperature of 80° C. to 110° C. and for a time of 3 to 8 hours.

9. The preparation method according to claim 6, characterized in that: The silane coupling agent is selected from one or more of methyltrimethoxysilane, methyltriethoxysilane, polymethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, octyltrimethoxysilane and octyltriethoxysilane; The amount of the silane coupling agent used is 0.1-10 wt % of the spherical porous silica.

10. The preparation method according to claim 6, characterized in that: The high temperature calcination temperature is 300° C. to 800° C., and the calcination time is 1 to 10 hours.

Citation Information

Patent Citations

  • Composition and method for preparing titanium dioxide-cerium dioxide composite molded product

    CN111450815A

Cited By

  • Zinc oxide composite sunscreen material based on mesoporous silica, and preparation and application thereof

    CN121041151A